Role of Vendor Responsiveness on Procurment Performance among Government Ministiries in Kenya - Chepngetich, Jesca; Achuora, John (My University, 2019)
Purpose: The main objective of the study was to examine the role of vendor responsiveness on procurement performance among government ministries in Kenya. Methodology: Descriptive research design was adopted. The study preferred this method because it allowed an in-depth study of the subject. The study used a sample size of 156 procurement staff. Census will be used in this study. Questionnaires were used to collect data. The questionnaires were tested for validity and reliability using 10% of the total sample respondents. Data was analysed through descriptive statistical methods such as means, standard deviation, frequencies and percentage. Inferential analyses were used in relation to correlation analysis and regression analysis to test the relationship between the four explanatory variables and the explained variable. Multiple regression models were used to show the relationship between the predicted variable and the predictor variables. Results: The findings of the study indicated that delivery time responsiveness, technical requirement responsiveness, financial requirement responsiveness and specifications requirement responsiveness have a positive relationship with procurement performance among government ministries Conclusion: Based on the study findings, the study concludes that performance of government ministries can be improved by delivery time requirement responsiveness, technical requirement responsiveness, financial requirement responsiveness and specifications requirement responsiveness. Policy recommendation: The study recommended that institutions should embrace vendor responsiveness measures so as to improve procurement performance and further researches should to be carried out in other institutions to find out if the same results can be obtained.
Keywords: Delivery time requirement responsiveness; Technical requirement responsiveness; Financial requirement responsiveness; Specifications requirement responsiveness